1993
DOI: 10.1128/mcb.13.2.891
|View full text |Cite
|
Sign up to set email alerts
|

Extinction of Oct-3/4 gene expression in embryonal carcinoma x fibroblast somatic cell hybrids is accompanied by changes in the methylation status, chromatin structure, and transcriptional activity of the Oct-3/4 upstream region.

Abstract: In this study we evaluate, for the first time, the molecular mechanism that underlies the extinction of a tissue-specific transcription factor, Oct-3/4, in somatic cell hybrids and compared it with its down-regulation in retinoic acid (RA)-treated embryonal carcinoma (EC) cells. The Oct-3/4 gene, which belongs to the POU family of transcription factors and is abundantly expressed in EC (OTF9-63) cells, provides an excellent model system with which to study the extinction phenomenon. Unlike other genes whose ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 60 publications
(54 reference statements)
2
37
0
Order By: Relevance
“…Expression of Oct4 is regulated at the transcription level by cis-acting elements located upstream of the Oct4 gene and methylation of chromatin structure (Fig 2B) [24]. By analyzing the expression of the LacZ reporter gene under the control of a 18Kb fragment from Oct4 genomic locus, Yeom et al identified two elements, which they named proximal enhancer (PE) and distal enhancer (DE) that may regulate the cell -type-specific expression of Oct4 ( Fig 2B) [25].…”
Section: Regulation Of Oct4 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of Oct4 is regulated at the transcription level by cis-acting elements located upstream of the Oct4 gene and methylation of chromatin structure (Fig 2B) [24]. By analyzing the expression of the LacZ reporter gene under the control of a 18Kb fragment from Oct4 genomic locus, Yeom et al identified two elements, which they named proximal enhancer (PE) and distal enhancer (DE) that may regulate the cell -type-specific expression of Oct4 ( Fig 2B) [25].…”
Section: Regulation Of Oct4 Expressionmentioning
confidence: 99%
“…One hypothesis is that the steady state level of Oct4 in totipotent cells may be a consequence of the establishment of active chromatin rather than the function of transcription activators. Ben-Shushan et al reported that the extinction of Oct4 activity in stem cells-fibroblast hybrid cells was accompanied by rapid methylation of regulatory sequences such as PE and DE in the Oct4 promoter/enhancer region [24]. Jaenisch suggested that there must be a wave of de novo methylation occurring in the somatic cells of the embryo [29].…”
Section: Regulation Of Oct4 Expressionmentioning
confidence: 99%
“…Oct-3/4 Methylation and Transcription-The Oct-3/4 gene undergoes de novo methylation both during embryogenesis (described above) and also in EC cells as a consequence of RA treatment (22). To find out if methylation plays a significant role in the regulation of Oct-3/4 gene expression, two kinds of experiments were performed.…”
Section: The Generation Of Oct-3/4 Methylation Pattern During Embryogmentioning
confidence: 99%
“…We have shown previously (22) that treatment of EC cells with RA reduces Oct-3/4 expression that is associated with increased methylation and changes in chromatin structure in the immediate upstream regulatory region that includes the promoter (P) and proximal enhancer (PE) elements. In this study we show that in vivo the Oct-3/4 gene is unmethylated from the blastula stage and starts to undergo de novo methylation at 6.5 dpc.…”
mentioning
confidence: 99%
“…Therefore, it is very likely that expression of Oct-3/4 plays an important role in determining early steps in embryogenesis and differentiation. Support for this notion was gained by showing that in EC ϫ fibroblast somatic cell hybrids, Oct-3/4 expression is suppressed, and reexpression of Oct-3/4 in these cells correlated with differentiation potential (2,61).…”
mentioning
confidence: 99%